Biomedical instrumentation and measurements - Cromwell, Leslie; Weibell, Fred J.; Pfeiffer, Erich A. (New Delhi : Prentice Hall of India, 2006)
Science General
Keywords: Biomedical instrumentation; Bioelectrnic protentials; Electrodes; Cardiovascular system; Patient care and monitiring; The nervous systems; Biotelemetry; X-Ray and radiostope instrumentatipn